Analysis of Carbon Footprint Reduction in Supply chains using Blockchains - Nechetnyy Nikita; Balassem Zaid Ajzan; subbarayudu Yerragudipadu; Goyal Wamika; Singh M.P.; Mittal Vaibhav; Sobti Sakshi; Sharma Gunjan; Nagaraju Krishna Chythanya (E3S Web of Conferences)
Integrating carbon footprint reduction into contemporary supply chain networks necessitates strong cybersecurity and data integrity protocols to safeguard communication infrastructures against threats. This study examines the use of blockchain technology as a cybersecurity and traceability framework in supply chain systems, using simulated data that represents logistical information, shipping quantities, carbon emissions, and blockchain transactions. An investigation indicates varied carbon-emitting mechanisms, with air freight exhibiting the greatest emissions and rail transit the lowest. Transportation nodes in Supply varying emission rates, with urban distribution centres generating more emissions than rural logistics hubs, underscoring disparities in carbon footprints across different areas. Moreover, risks such data breaches, illegal access, and cyberattacks underscore the fragility of centralized supply chain systems. Blockchain transactions exemplify secure and transparent exchanges throughout all of the supply chain, highlighting blockchain’s capacity to provide safe and verifiable monitoring of carbon emissions inside the network. This research Supply the potential of blockchain technology to diminish carbon footprints in supply chains, emphasizing its ability to enhance data security, authenticate carbon emission assertions, and augment traceability. The findings highlight the need for customized cybersecurity frameworks for Supply demonstrate blockchain’s capacity to improve the transparency, security, and sustainability of global supply chain operations.